Optical characterization of amorphous oligo(4,4′-biphenylene-1,1-substituted methylene)s - del Rosso, Pablo Gabriel (2007)
Oligo(p-biphenylene-1,1-substituted methylene)s with p-biphenylene units tethered along the oligomer main chain by their para positions to isopropylene, perfluoroisopropylene, cyclohexylene or fluorenylene spacers were synthesised from dimesylates using the Ni homocoupling reaction. GPC, NMR, DSC and POM techniques showed that they are amorphous with high Tg and have low polydispersity indexes, few residual end groups and good solubilities. The materials are UV-absorbers and emitters with good film-forming properties. The increase in size or polarity of the isopropylidene spacer does not bring major changes in their optical properties while the introduction of a fluorene spacer substantially modifies its optical response. Their absorption and emission behavior indicated that the spacers isolate the gem-biphenyls and the small differences observed in absorption maxima can be assigned to substitution effects instead of homoconjugative effects. No aggregate formation was detected by red-edge excitation experiments indicating that their contorted chain conformations hinder interactions between the biphenylene chromophores although the fluorenylene-spaced oligomer form fluorene excimers. Fluorescence anisotropy indicated that all these disordered cromophoric assemblies have high bulk exciton mobilities. The propylidene-spaced oligomer is very efficient as a donor for energy transfer.